2004
DOI: 10.1248/bpb.27.1576
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Some Pentacyclic Triterpenes and Their Synthesized 3-O-Lipophilic Chains

Abstract: The pentacyclic triterpenes of ursane and oleanane skeletons found to accumulate in a number of terrestrial plants in free or glycosidic form.1) Some of these metabolites such as amyrins and ursolic acid have been reported as the bioactive constituents from a number of plants used in traditional and folk medicine.2,3) Amyrins were found to exhibit interesting pharmacological activities such as anti-inflammatory, 4,5) antiproteolytic, 6) antifungal 7) etc. whereas, ursolic acid was found to exhibit significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 17 publications
3
47
0
1
Order By: Relevance
“…The NMR spectra of 1 are in accordance with data reported in the literature for 3ÎČ-E-coumaroylbetulinic acid (1) [17]; 2 for lupeol fatty acid esters [18], 3 for betulonic acid [19], 4 for betulin [20], 5 for betulinic acid [21], 6 for lupeol [16], 7 for lupenone [22], 8 for 3ÎČ-E-feruloyllupeol [2], 9 for 3ÎČ-Zferuloyllupeol [2], and 10 for chlorophyll a [23].…”
Section: Resultssupporting
confidence: 87%
“…The NMR spectra of 1 are in accordance with data reported in the literature for 3ÎČ-E-coumaroylbetulinic acid (1) [17]; 2 for lupeol fatty acid esters [18], 3 for betulonic acid [19], 4 for betulin [20], 5 for betulinic acid [21], 6 for lupeol [16], 7 for lupenone [22], 8 for 3ÎČ-E-feruloyllupeol [2], 9 for 3ÎČ-Zferuloyllupeol [2], and 10 for chlorophyll a [23].…”
Section: Resultssupporting
confidence: 87%
“…UA extracted from Diopsyros melanoxylon (Ebenaceae) and its liophylic 3-O fatty acids ester chains (C 12 -C 18 ) were evaluated for antimicrobial activity against Pseudomonas syringae, Bacillus sphaericus, Bacillus subtilis, E. coli and Salmonella typhi and moderate activity was reported [56] (Table 1). Also Chattopadhyay and coworkers found that n-butanol extracts of Alstonia macrophylla (Apocyanaceae) [57] and Mallotus pelatus (Euphorbiaceae) [58], enriched in UA and used in South Asian traditional medicine, showed moderate antibacterial activity against…”
Section: Antibacterial Activity Of Ua and Its Derivativesmentioning
confidence: 99%
“…Both oleonolic acid and ursolic acid, which are rather similar because of the closeness of their chemical structures, have many important pharmacological effects. The literature includes numerous data on anti-inflammatory (Safayhi & Sailer, 1997), antitumor (Ovesna et al, 2004), anti-HIV (Kashiwada et al, 1998), antimicrobial (Mallavadhani et al, 2004. ), antifungal (Rocha et al, 2004), hypoglycemic (Perez et al, 1998) and antihyperlipidemic (Ma, 1982) properties.…”
Section: Discussionmentioning
confidence: 99%